A novel function for HEG1 in promoting metastasis in hepatocellular carcinoma. (11th October 2019) - Dewdney, Brittany; Hebbard, Lionel
Abstract: Hepatocellular carcinoma (HCC) remains one of the leading causes of cancer-related deaths around the globe. For patients receiving liver tumour resection, the risk of reoccurrence and metastasis is high. Cancer metastasis can occur as a consequence of a physical change known as epithelial to mesenchymal transition (EMT). In this instance, cancer cells acquire migratory and invasive characteristics that allow the cells to move into adjacent tissue or enter the bloodstream to reach a secondary site, where they begin to form a new tumour. Targetting proteins involved in the signalling pathways that induce the mesenchymal phenotype has been an ongoing field of research. A recently published study has described a novel role for the heart development protein with EGF-like domains (HEG1) in promoting EMT. This research provides new insights into the biological function of this protein in HCC. Furthermore, the research indicates a new target for future prognostic and therapeutic research in HCC.